In the era of corona virus: health care professionals' knowledge, attitudes, and practice of hand hygiene in Saudi primary care centers: a cross-sectional study - Ali Alfahan; Samia Alhabib; Imad Abdulmajeed; Saeed Rahman; Samira Bamuhair (Greater Baltimore Medical Center, 2016)
Background: Hand hygiene is one of the essential means to prevent the spread of infections. The aim of this study was to assess the knowledge, attitudes, and practice (KAP) of hand hygiene in primary care settings. Methods: A cross-sectional study using a self-reported questionnaire was conducted in primary care settings located in Riyadh, Kingdom of Saudi Arabia, under the service of King Abdulaziz Medical City (KAMC). The Institutional Review Board of KAMC Research Centre approved the study. Data were analyzed using IBM SPSS software. Results: A total of 237 participants were included in the analysis. Participants who received hand hygiene training within the last 3 years (2012-2014) scored higher on a knowledge scale. Generally, there was an overall positive attitude from participants toward hand hygiene practice. In total, 87.54% acknowledged that they routinely used alcohol-based hand rub, 87.4% had sufficiently decontaminated hands even under high work pressure, and 78.6% addressed that this practice was not affected by less compliant colleagues. Conclusion: Practicing hand hygiene was suggested to be influenced by variables related to the environmental context, social pressure, and individual attitudes toward hand hygiene. We believe that addressing beliefs, attitudes, capacity, and supportive infrastructures to sustain hand-hygiene routine behaviors are important components of an implementation strategy in enhancing health care workers' KAP of hand hygiene.